2002
DOI: 10.1046/j.1365-2036.2002.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of pantoprazole vs. nizatidine in the treatment of erosive oesophagitis: a randomized, active‐controlled, double‐blind study

Abstract: SUMMARYBackground: Pantoprazole is a proton pump inhibitor approved for the treatment of erosive oesophagitis and gastro-oesophageal reflux disease. Aim: To compare the efficacy and safety of pantoprazole vs. nizatidine for the treatment of symptomatic gastrooesophageal reflux disease and endoscopically documented erosive oesophagitis (grade ‡ 2). Methods: A multicentre, double-blind, randomized, active-controlled study (221 patients) was performed to compare 20 and 40 mg pantoprazole daily with nizatidine 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
2
22
0
2
Order By: Relevance
“…PPIs are the current treatment of choice for patients with GERD; PPI treatment provides the most rapid symptomatic control of all available agents, and this study is in accordance with the literature showing that treatment effect can be achieved within a matter of days [1, 2, 29, 30]. In patients with erosive GERD, Castell et al [22] reported a median time to first resolution of diary-recorded heartburn of 2 days and a median time to sustained resolution of diary-recorded heartburn of 7 days, with 40 mg esomeprazole (ITT population).…”
Section: Discussionsupporting
confidence: 85%
“…PPIs are the current treatment of choice for patients with GERD; PPI treatment provides the most rapid symptomatic control of all available agents, and this study is in accordance with the literature showing that treatment effect can be achieved within a matter of days [1, 2, 29, 30]. In patients with erosive GERD, Castell et al [22] reported a median time to first resolution of diary-recorded heartburn of 2 days and a median time to sustained resolution of diary-recorded heartburn of 7 days, with 40 mg esomeprazole (ITT population).…”
Section: Discussionsupporting
confidence: 85%
“…Among conventional medications, proton pump inhibitors (PPIs) are by far the most potent medications for treating reflux esophagitis, especially erosive esophagitis, because of their potent acid suppression effect [1]. Effects of PPIs on erosive esophagitis have been studied in randomized controlled trials [5][6][7][8]. In general, those studies demonstrated a high healing rate (83-94%) of erosive esophagitis in those treated by PPI for 8 weeks and a relatively lower healing rate (64-82%) at 4 weeks [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Published studies have demonstrated that 40 mg of pantoprazole orally once a day was effective for treating erosive esophagitis [7] and was superior to nizatidine [8]. Pantoprazole is one of the few PPIs available on the US market for intravenous administration.…”
Section: Introductionmentioning
confidence: 99%
“…Oral pantoprazole, a proton pump inhibitor (PPI), is efficacious in healing erosive esophagitis (EE) and controlling associated symptoms [1,2]. Additional studies have demonstrated efficacy in maintaining healing of EE and preventing recurrence of GERD symptoms over 1 year of treatment [3,4].…”
Section: Introductionmentioning
confidence: 99%